Changes in qualities of dried Zanthoxylum armatum DC. at different storage methods. (September 2021) - Cheng, Jinxi; Ke, Jingxuan; Hou, Xiaoyan; Li, Shanshan; Luo, Qingying; Shen, Guanghui; Wu, Hejun; Li, Meiliang; Liu, Xingyan; Chen, Anjun; Zhang, Zhiqing
Graphical abstract: Highlights: Light, oxygen and temperature affected the Zanthoxylum armatum DC. qualities greatly. Zanthoxylum armatum DC. showed good quality at −18 °C in vacuum and non-light package. Image analysis was applied to record the color change of Zanthoxylum armatum DC. Colorimetric method could compare the color change of Zanthoxylum armatum DC. Abstract: This study investigated the impact of different storage conditions on the qualities of dried Z. armatum, including color, numbness, and aroma, for seven months to identify a suitable storage method. The storage conditions (n = 12) included four kinds of packaging methods, namely vacuum and non-light packaging (VnL), vacuum and light packaging (VL), ventilation and non-light packaging (K), non-vacuum and light packaging (nVL) stored at different temperature, room temperature, 0−4 °C, and −18 °C. The results showed that temperature affected the most of its qualities. There was a significant reduction in the qualities of Z. armatum at room temperature, however, at −18 °C, the contents of chlorophyll, hydroxy- α -sanshool, and linalool in Z. armatum were found to be retained at 1.33–1.37 mg/g, 21.24–23.64 mg/g, and 64.53–67.29 μL/mg at the seventh month, respectively. Light also played an important part in deteriorating the qualities of Z. armatum . At room temperature, the contents of chlorophyll, hydroxy- α -sanshool, and linalool in the VnL were higher than those in the VL. Additionally, oxygen also affected the color and numbness in Z. armatum but had little effect on aroma. At room temperature, the contents of chlorophyll and hydroxy- α -sanshool in the VnL and K were 1.11 mg/g and 1.03 mg/g, 19.10 mg/g and 11.95 mg/g at the seventh month, respectively. However, the trends of linalool loss in the VnL and K were almost the same during storage. Therefore, the optimal way to preserve dried Z. armatum was VnL at −18 °C.